Surgical Orthodontics: A Case Report - Mohamed, Wael; Hassan, Rozita; Ab. Rahman, Shaifulizan (IIUM Medical Journal Malaysia, 2017)
Introduction: Duration of treatment is one of the things orthodontic patients complaint about most and challenging orthodontist to shorten treatment time. A new surgical technique was introduced to accelerate tooth movement during orthodontic treatment through combining surgical and orthodontic treatment by doing surgical reduction of the bone mass in the path of desired tooth movement prior to start orthodontic alignment of the teeth. This case report showed treatment of 21 years old male patient complaint of teeth malalignment and he requested to finish treatment in short time. Upper right first premolar and lower left second premolar were extracted, all the bones in the desired path of tooth movement was removed and the dentoalveolar distraction procedure was performed using Nickel Titanium closing coil spring and power chain. Complete teeth alignment was achieved in two months period and the anchorage teeth were able to withstand the retraction forces with minimal anchorage loss.